Problems of interpreting the Iraqi Constitution in light of the decisions of the Federal Supreme Court, a critical analytical study - Mawlud, Muhammed Omer (Journal of Legal and Political Studies, 2024)
There is no doubt that the interpretation of the constitution which is considered as the most important legal document of the state, and the supreme law in the country, occupies a great importance, because the constitution includes stipulating general authorities in the state and the limits of the competences and powers of each of them, it also includes the text on the general rights and freedoms of individuals. and that the constitution as legal document contains ambiguous texts, may be subject of different interpretations. and here comes the role of the judiciary which is considered the competent authority to interpret the constitution. and in Iraq the Federal supreme court is competent to interpret the constitution in accordance with the provisions of article (93- second) of the constitution of Iraq for the year 2005. and in this research after we clarified the nature of the interpretation, we talked about the Federal supreme court in Iraq, despite the passage of more than eighteen years the entry into force of the constitution article (92) of it has not been applied by issuing a law that includes its formation in accordance with the with amending the old court law No. (30) of 2005 which cast doubt on the legitimacy of this court. As it become clear to us through the decisions of this court since its formation until the writing of these lines, that this court was not at the level of ambition, but rather it interpreted some provisions of the constitution in a manner contrary to what was stated in it despite its clarity and categorical implications, which made it the subject of criticism by many law professors, specialists, and researchers in this regard.
Keywords: Constitution 2005 Federal Supreme Court Internal Regulations Free Scientific Doctrine Amended Interpretation of the Constitution